Challenges of Diffusion Bonding of Different Classes of Stainless Steels. Issue 2 (23rd October 2017) - Gietzelt, Thomas; Toth, Volker; Huell, Andreas
Abstract : Solid state diffusion bonding is used to produce monolithic parts exhibiting mechanical properties comparable to those of the bulk material . This requires diffusion of atoms across mating surfaces at high temperatures, accompanied by grain growth . In case of steel, polymorphy helps to limit the grain size, since the microstructure is transformed twice. The diffusion coefficient differs extremely for ferritic and austenitic phases. Alloying elements may shift or suppress phase transformation until the melting range. In this paper, diffusion bonding experiments are reported for austenitic, ferritic, and martensitic stainless steels possessing varying alloying elements and contents. Passivation layers of different compositions are formed, thus affecting the local diffusion coefficient and impeding diffusion across faying surfaces. As a consequence, different bonding temperatures are needed to obtain good bonding results, making it difficult to control the deformation of parts, since strong nonlinearities exist between temperature, bonding time, and bearing pressure. For martensitic stainless steel, it is shown that it is very easy to obtain good bonding results at low deformation, whereas ferritic and austenitic stainless steels require much more extreme bonding parameters. Abstract : Diffusion bonding is employed for full cross‐sectional joining of complex geometries. The graphical abstract shows a part for ITER (International Thermonuclear Experimental Reactor) made of austenitic stainless steel, containing 3D cooling structures. Thermally stable passivation layers make it difficult to form a monolithic part. Employing a self‐stabilizing design, the bonding area is increased with process time, allowing to control deformation.